Growth and Financing of Elementary Education in Uttar Pradesh:A Province in India - Rani, P. Geetha (Education Policy Analysis Archives, 2004)
The present article attempts to study financing patterns of elementary education in Uttar Pradesh. A review of educational development in the state reveals that the goal of universalizing elementary education in a resource-poor state seems to be elusive in the near future. Neither the financing pattern of education per se nor elementary education in particular is conducive to achieving the target of universal elementary education. The magnitude of out-of-school children (leaving or dropped-out children) vis-à-vis the resources allocated toward elementary education provides a gloomy picture in the state. Financing the additional resources required to universalize elementary education in the state would require significant reallocations in overall expenditure with federal assistance, since the fiscal situation in Uttar Pradesh is highly imbalanced. The state and central government should bear the entire responsibility of funding and ensure the twin principles of equity and efficiency in the public education system in the state. This requires an indomitable political commitment in terms of reorientation of spending priorities and improving the efficiency of resource use in the state. This study reaffirms that the goal of universal elementary education could become a reality only if there is a joint commitment between the federal and state polities.